Global, regional, and national burden of tuberculosis due to smoking, 1990-2021: analysis for the Global Burden of Disease study - Zhao, Guizeng; Wu, Yating; Song, Chen; Sun, Yazhou; Zang, Shuzhi; Tian, Feng; Gao, Zhitao; Zhang, Chenguang; Wang, Xia (Frontiers in Immunology, 2025)
BackgroundTuberculosis (TB) is an infectious disease caused by Mycobacterium tuberculosis invading the lungs and other organs, which is a serious threat to human life and health. Recent studies have shown that smoking is an important risk factor for the development of TB and advances the progression of TB through multiple mechanisms that affect the body’s immune function.MethodsA multidimensional analytical approach was taken to gain a comprehensive understanding of the burden of disease. First, the burden of TB due to smoking (Deaths, DALYs, YLDs, and YLLs) from 1990–2021 was conducted. And then, differences in the burden of disease in 2021 were explored across gender, age, SDI regions, GBD regions and countries. In addition, decomposition analysis was performed to understand the influencing factors of disease burden. Finally, ARIMA and ES models were used to predict trends in disease burden from 2022-2050.ResultsGlobally, the number of cases and ASR of TB due to smoking have decreased over time. The burden of disease is heaviest in the middle-aged male population and is much higher than in women. The burden is higher in regions with lower levels of SDI than in those with higher levels of SDI. Australasia has the lowest burden, while India is the country with the highest burden. Projections show a general downward trend in the number of disease burdens from 2022 to 2050, but there is still a need to develop the right strategies to meet the challenges of disease.ConclusionsSmoking as an independent risk factor for several chronic diseases, this study focuses on the burden of TB due to smoking. Although the results show that the burden situation is decreasing year by year, the state and society still need to increase the publicity of science, raise the awareness of the disease among the public, and develop public health programs to deal with the disease.